Effects of oxyethylated glycerol cryoprotectants on phase transitions of DPPC model membranes - Kasian, N.A.; Krasnikova, A.O.; Vashchenko, O.V.; Lisetski, L.N.; Zinchenko, A.V.; Kompaniets, A.M.; Ratushna, M.V. (Вiopolymers and Cell, 2015)
Aim. To determine the effect of the oxyethylated glycerol cryoprotectants (OEGn) with polymerization degrees n = 5, 25, 30 on the phase states and phase transitions of dipalmitoylphosphatidylcholine (DPPC)-based model membranes. Methods. Differential scanning calorimetry. Results. Model lipid membranes on water/OEGn and water/glycerol subphases with varying cryoprotectant concentrations from 0 to ~ 100 % w/w were studied. A significant raise in the pre-transition and main phase transition temperatures with increasing OEGn concentration was noted whereas the membrane melting peak persist to 100 % w/w OEGn. A sharp increase in the melting enthalpy was observed for OEGn = 5. Conclusions. The solvating ability of the subphase in DPPC membranes decreases in the order water > glycerol > OEGn = 5 > OEGn = 25 > OEGn = 30, which correlates with the relative number of groups effectively contributing to the solvation process.